2013
DOI: 10.3758/s13423-013-0460-x
|View full text |Cite
|
Sign up to set email alerts
|

The Gestalt principle of similarity benefits visual working memory

Abstract: Visual working memory (VWM) is essential for many cognitive processes yet it is notably limited in capacity. Visual perception processing is facilitated by Gestalt principles of grouping, such as connectedness, similarity, and proximity. This introduces the question: do these perceptual benefits extend to VWM? If so, can this be an approach to enhance VWM function by optimizing the processing of information? Previous findings demonstrate that several Gestalt principles (connectedness, common region, and spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
127
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(149 citation statements)
references
References 44 publications
21
127
1
Order By: Relevance
“…These data support and largely extend the existing evidence (e.g., Jiang et al, 2000;Kemps, 2001;Peterson & Berryhill, 2013;Woodman et al, 2003;Xu & Chun, 2007) showing that Gestalt principles of perceptual organization, like the tendency to perceive and interpret environment in the simple, orderly, and regular way (Law of Pragnanz), and the influence of such attributes of perceptual objects as proximity, similarity, closure, and continuity for their grouping into coherent wholes, which are well-known to organize visual perception, influence also the active maintenance and access of information in VWM during the absence of perceptual stimulation. These results have crucial significance for our understanding of the mechanisms and function of one of the crucial elements of human mind architecture -working memory (i.e., its visual component).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…These data support and largely extend the existing evidence (e.g., Jiang et al, 2000;Kemps, 2001;Peterson & Berryhill, 2013;Woodman et al, 2003;Xu & Chun, 2007) showing that Gestalt principles of perceptual organization, like the tendency to perceive and interpret environment in the simple, orderly, and regular way (Law of Pragnanz), and the influence of such attributes of perceptual objects as proximity, similarity, closure, and continuity for their grouping into coherent wholes, which are well-known to organize visual perception, influence also the active maintenance and access of information in VWM during the absence of perceptual stimulation. These results have crucial significance for our understanding of the mechanisms and function of one of the crucial elements of human mind architecture -working memory (i.e., its visual component).…”
Section: Resultssupporting
confidence: 88%
“…Some studies have demonstrated that satisfying such principles by the group of objects not only helps in perceiving them in a particular way, but also facilitates their retrieval from VWM (that is, Gestalt principles "work" even when objects are not accessible perceptually). For instance, objects displayed in proximity to an object that had been cued were more likely reported than distant objects (Woodman, Vecera, & Luck, 2003), and the overall number of reported objects was larger if they were grouped in preceding display than when they were not grouped (Xu & Chun, 2007; for an analogous result pertaining to grouping by similarity see Peterson & Berryhill, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Anderson et al (2013) induced perceptual grouping by illusory contours that depended on the rotation of Pac-Man-like inducers and found that VWM for the rotation of single inducers improved when an illusory contour was formed. Similarly, in studies that have investigated the grouping of items on the basis of color, VWM performance was measured by color judgments (Brady et al, 2009;Peterson & Berryhill, 2013). By contrast, in the present study, memory performance was assessed through exemplar-level object discrimination, whereas the grouping was based on spatial relations and, importantly, on the object-category level.…”
Section: Discussionmentioning
confidence: 92%
“…However, this effect could partly reflect low-level Gestalt grouping, which is known to enhance VWM (Anderson et al, 2013;Peterson & Berryhill, 2013;Woodman et al, 2003;Xu, 2006;Xu & Chun, 2007). Although we carefully selected our stimuli to avoid the regular and irregular object pairs differing along low-level dimensions, in Experiment2 we included a control condition to directly rule out any influence of such putative low-level differences.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation